Proteosome-adjuvanted intranasal influenza vaccines: advantages, progress and future considerations. (March 2011) - Burt, David; Mallett, Corey; Plante, Martin; Zimmermann, Joseph; Torossian, Krikor; Fries, Louis
The development of a safe and effective non-live intranasal influenza vaccine has been an elusive target in vaccinology for many decades. It is perceived that intranasal immunization, by offering a more convenient and less invasive vaccination modality, will boost vaccination rates against influenza, a disease that continues to inflict a significant annual health and economic burden worldwide. Intranasal immunization may also confer additional immunoprotective benefits by eliciting mucosal secretory antibodies at the site of entry of the virus, which are typically more broadly cross-reactive and cross-protective compared with those induced by systemic routes of vaccination. This property is highly desirable for confering improved protection against variant strains of influenza virus. Here we review the current status of intranasal proteosome-based influenza vaccines that comprise commercial detergent-split influenza antigens and proteosome adjuvants derived from purified bacterial outer membrane proteins. We demonstrate that these vaccines exhibit the desired advantages expected from immunization via the intranasal route. Furthermore, in clinical trials proteosome-based influenza vaccines were shown to be safe and protective in humans. The future possibilities for commercializing intranasal proteosome––influenza vaccines are also discussed.